Strategi Penanganan Keamanan Siber Di Indonesia - Tedi Ramadhan; Risky Pujianto; Fahrul Bagus Santoso (Journal of Informatic and Information Security, 2024)
This study continues previous research focused on cybersecurity issues in Indonesia. Its objective is to analyze cybersecurity challenges within the framework of strategies implemented by the Indonesian government. The evolution of cyber threats in the country is examined from the perspective of cybersecurity and national defense, which formed the basis of earlier research, and further expanded to explore relevant mitigation strategies.To provide a comprehensive understanding, this study adopts a three-perspective model that maps cyberspace into various logical layers. The research begins by highlighting the condition of Indonesian netizen and the challenges they face, then links these findings to the state’s perspective in the context of defense, as well as the connections with the public sector, private sector, and international community.